2011
DOI: 10.21608/jappmu.2011.83347
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance, Carcass Characteristics and Some Haematological Constituents of Japanese Quails Fed Diets Containing Different Levels of Sunflower and Sesame Meal as a Replacement of Soybean Meal

Abstract: This study was conducted to investigate the effect of replacing soybean meal (SBM) by locally available oilseed meals i.e., sunflower seed meal (SFM) and sesame seed meal (SSM) at different substitution levels 25, 50 and 100% on an isonitrogenous and isocaloric basis. A total number of 315 mixed sex 7 th days-old Japanese quails were randomly distributed into 7 treatment groups of 45 birds each, with three replicates containing 15 birds each. The experiment was carried out for 42 days (from7th to 48 th days of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Abdel‐Hakim et al . (2011) also reported an inverse correlation between CP and crude fibre in sunflower meal.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Abdel‐Hakim et al . (2011) also reported an inverse correlation between CP and crude fibre in sunflower meal.…”
Section: Resultsmentioning
confidence: 90%
“…Crude fibre was inversely correlated (r = À0.97) to the CP and positively correlated (r = 0.95) to crude fat for all varieties and locations. Abdel-Hakim et al (2011) also reported an inverse correlation between CP and crude fibre in sunflower meal.…”
Section: Nutritional and Tia Levels Between Two Varieties Of Soybeansmentioning
confidence: 86%